2020
DOI: 10.3390/foods9091309
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Mixing Milk of Different Species on Chemical, Physicochemical, and Sensory Features of Cheeses: A Review

Abstract: The yield and quality of cheese are associated with the composition, physicochemical, sensory, rheological, and microbiological properties of milk and with the technology applied to the milk before and/or during cheese processing. This review describes the most important research on cheeses obtained from processing mixtures of different milk species and discusses the effect of milk mixtures (i.e., species and mixture ratios) on composition, physicochemical, sensory, rheological, and microbiological properties … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 92 publications
1
17
0
Order By: Relevance
“…Our literature review revealed that it has been fully demonstrated by different authors that the knowledge of how (i) the animal species from which the milk originates and (ii) the proportions of each species of milk used in the mixture influence the quality of yoghurt. Similarly, proportions necessary to design targeted products with improved physicochemical, nutritional, functional and sensory qualities are also discussed and corroborated with those highlighted in our previous review on cheese [108].…”
Section: Conclusion and Future Trendssupporting
confidence: 75%
“…Our literature review revealed that it has been fully demonstrated by different authors that the knowledge of how (i) the animal species from which the milk originates and (ii) the proportions of each species of milk used in the mixture influence the quality of yoghurt. Similarly, proportions necessary to design targeted products with improved physicochemical, nutritional, functional and sensory qualities are also discussed and corroborated with those highlighted in our previous review on cheese [108].…”
Section: Conclusion and Future Trendssupporting
confidence: 75%
“…The CaM and CM mixtures were prepared after each milk sample was warmed to 40°C using a water bath and gently mixed by hand for at least 1 min. The volume fractions (%) of CaM in the different formulations were performed according to previous reviews of Boukria, El Hadrami, Boudalia, et al (2020) and Boukria, El Hadrami, Sameen, et al (2020), which were fixed at 100% (i.e., CaM), 75% (i.e., 3CaM:1CM, v/v), 50% (i.e., 1CaM:1CM, v/v), 25% (i.e., 1CaM:3CM, v/v), and 0% (i.e., CM). Milk coagulations were performed at 40°C (±1°C) using 0.25 µl/ml of CHY-MAX® M (Chr.…”
Section: Milk and Milk Coagulationmentioning
confidence: 99%
“…They choose between the lipid and protein components of milk and those present in cheese, such as fatty acids, caseins, and whey proteins. The Food Industry usually seeks to increase milk protein, especially casein, which is considered to be the best quality [84]. Likewise, the growing demand for gluten-free products has encouraged the design of many gluten-free bakery products [85].…”
Section: Topics Of the Publications Cited In Patentsmentioning
confidence: 99%